ITIKAF RAMADHAN SEBAGAI MEDIUM INTERNALISASI AKHLAK ISLAMI DAN KONTRIBUSI SOSIAL DI LINGKUNGAN KAMPUS - Wahidah, Yelis Nur (LPPM STAI Al-Azhary Cianjur, 2025)
Ramadan Iktikaf is a spiritually rich act of worship that serves not only as a means of drawing closer to God but also as a medium for character development and social awareness. In the campus context, iktikaf creates a reflective space where spiritual, educational, and participatory dimensions converge across diverse backgrounds. This study aims to examine the implementation of Ramadan iktikaf at Ulil Albab Mosque, Islamic University of Indonesia, particularly in relation to the internalization of Islamic moral values and the social contribution of participants. A descriptive qualitative approach was employed through interviews, participant observation, and documentation. The findings reveal that iktikaf was managed systematically and inclusively, providing a profound spiritual experience while cultivating social concern. The internalization of values occurred through habituation, role modeling, and direct experience within an intensive spiritual setting. Post-iktikaf, participants demonstrated personal transformation and increased social engagement within the campus environment. A positive correlation was identified between the intensity of participation and the enhancement of moral character and social ethos. These findings affirm that iktikaf can serve as an effective strategy for character education in Islamic higher education settings.